Complex patterns of WNV evolution: a focus on the Western Balkans and Central Europe - Šolaja, Sofija; Goletić, Šejla; Veljović, Ljubiša; Glišić, Dimitrije (Frontiers in Veterinary Science, 2024)
IntroductionWest Nile Virus, an emerging zoonotic pathogen, has been circulating in Serbia for over a decade, with its first detection in mosquitoes in 2010. Since then, the virus has led to increasing cases in both animals and humans, peaking in 2018 with 415 human cases and 36 fatalities. This study aimed to explore the phylogenetic relationships between previously sequenced West Nile virus strains from Serbia and those sequenced in this study, while also identifying possible virulence factors.Materials and methodsWhole genome sequencing was conducted using a targeted approach on the MinION Mk1C platform, following a two-step process involving cDNA synthesis and amplification. Bioinformatics analysis included demultiplexing, primer trimming, and sequence mapping using tools such as iVar, Minimap2, and Samtools. Phylogenetic analysis was performed using MAFFT alignment and the Maximum Likelihood method with the Tamura Nei model in MEGA X software. Virulence factors were assessed in both structural and nonstructural proteins, focusing on key glycosylation motifs and specific mutations. Homology modeling of the E protein was also performed to evaluate potential structural changes due to mutations.ResultsPhylogenetic analysis revealed two major sublineages within the E subclade, representing the majority of strains from Western and Central Europe. These sublineages likely originated from Austria, Serbia, and Hungary between 2008 and 2012. The study also identified three distinct sublineages within the D subclade, which includes more diverse strains from Southern Europe. The E protein exhibited significant variations, particularly at the E159 site, which is crucial for virulence. The EI159T aa change has become dominant in recent years, replacing the previously prevalent EI159M. Additionally, changes in the NS1 glycoprotein and NS3 protein, both of which are involved in immune modulation and viral replication, were identified, with potential implications for the virus’s virulence.ConclusionThe study’s findings highlight the Western Balkans and Central Europe as key regions for the mixing and dissemination of West Nile virus strains from both Western-Central and Southern Europe. These results underscore the importance of continuous surveillance and phylogenetic analysis to monitor the evolution and spread of West Nile virus, particularly in light of the frequent mutations observed in virulence-associated sites.